Efisiensi Pengeluaran Bulanan dalam Perspektif Manajemen Keuangan Pribadi: Temuan Empiris pada Penghuni Kos - Rahayu Rizki Ramadhani; Enik Rahayu (Journal of Education, Humaniora and Social Sciences (JEHSS), 2026)
This article aims to describe and analyze monthly expenditure efficiency from the perspective of personal financial management among boarding house residents. The problem focuses on how budgeting, expenditure control, financial recording, and priority setting are practiced by residents under limited income conditions. To address this issue, this study is grounded in personal financial management theory and behavioral finance theory, which explain individual financial decision-making processes in daily life. Data were collected through in-depth interviews, non-participant observation, and documentation involving eight residents of Azriel Randugunting Boarding House selected purposively, and were analyzed qualitatively using thematic analysis. The findings indicate that monthly expenditure efficiency is strongly influenced by the quality of personal financial management practices. Residents who consistently apply budgeting and financial recording tend to maintain a balance between income and expenses, while those without financial planning are more vulnerable to inefficient spending. Empirically, this study contributes by highlighting that boarding house residents as a group with limited financial resources, exhibit distinctive financial management behaviors, where expenditure efficiency is shaped more by financial discipline and awareness than by income level itself.